Conocimiento sobre el fondo de ahorro para el retiro de usuarios en Ciudad Juárez, México - Hernández Lozano, Francisco Arturo; Solís Rodríguez, Fany Thelma; Soltero Puentes, Luis Brandon (2020)
The level of knowledge of financial education that users have about the savings fund for their retirement work is crucial. In Mexico, such knowledge is generally scarce, according to studies in this regard. This work is the product of an investigation that aimed to determine the level of knowledge that users who come to the National Commission for the Protection and Defense of Users of Financial Services (in Spanish Condusef) in Juarez, Mexico. The methodology consisted of a descriptive, cross-cutting research with quantitative approach using the survey's information collection technique. The schooled assessment of 0 to 10 of the national education systems was used as a standard measure to determine a knowledge level score, where the average of six is at least approving. The results yielded averaged 5.3, which according to the school evaluation is considered a non-approval rating and insufficient knowledge level on the subject. In addition, information was obtained from users about their financial decisions regarding how they will solve their expenses in old age, on quality of life problems at the stage of retirement and whether they will receive a pension. Therefore, it is essential that the Condusef's care units continue in their mission to promote and disseminate financial education at all levels of education so that users make informed decisions about their job retirement.